Keberadaan Pagar Laut di Wilayah Kabupaten Bekasi: Respon Masyarakat dan Dampak yang Ditimbulkan - Aulia, Muhammad Fikriansyah; Zid, Muhammad; Seta, Ananto Kusuma; Setiawan, Cahyadi (ARZUSIN, 2025)
The construction of illegal sea fences in Tarumajaya District, Bekasi Regency, has restricted fishermen's access to marine resources, triggering environmental degradation, economic decline, and social conflict. This study aims to analyze the impacts of sea fence construction in Bekasi Regency from environmental, social, and economic aspects, as well as the responses of coastal communities in Bekasi Regency. This research uses a qualitative approach to explore the social and economic dynamics of coastal communities through observations in Tarumajaya District, Bekasi Regency, as well as in-depth interviews with fishermen, policymakers, and affected communities. The findings reveal that, from a social perspective, the sea fences have triggered horizontal conflicts among fishermen due to competition over fishing grounds and have led to social exclusion, worsening the welfare of coastal communities. From an economic standpoint, reduced catches have caused a decline in fishermen's incomes and forced some to switch professions, though alternative job options often lack comparable stability.